2020
DOI: 10.1002/ar.24362
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of CDK6 expression by microRNA‐126‐5p and its influence on the proliferation and invasion of esophageal cancer cells

Abstract: The present study aimed to investigate the expression of cyclin-dependent kinase 6 (CDK6) and microRNA-126-5p (miR-126-5p) in esophageal cancer tissues and cells, and their effect on esophageal cancer cell proliferation and invasion, and to explore the potential molecular mechanisms. The relative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Fiala et al 17 found that miR-126-5p expression was significantly associated with progression-free survival and overall survival in metastatic colorectal cancer. In another study, Gu et al 18 explored the relationship between miR-126-5p and esophageal cancer cells and observed that miR-126-5p could target CDK6 and has a positive role in inhibiting the proliferation and migration of esophageal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Fiala et al 17 found that miR-126-5p expression was significantly associated with progression-free survival and overall survival in metastatic colorectal cancer. In another study, Gu et al 18 explored the relationship between miR-126-5p and esophageal cancer cells and observed that miR-126-5p could target CDK6 and has a positive role in inhibiting the proliferation and migration of esophageal cancer cells.…”
Section: Discussionmentioning
confidence: 99%